PERAN BUMDES DALAM PENINGKATAN PEREKONOMIAN MASYARAKAT MELALUI PASAR TAWANG DI DESA TAWANGREJO KECAMATAN KUNDURAN KABUPATEN BLORA - Falah, Miftachul; Ilovia Aya Regita Widayat; Miladia Fadilasari (LPPM STAI Muhammadiyah Probolinggo, 2026)
Village-Owned Enterprises (Badan Usaha Milik Desa / BUMDes) play a strategic role in supporting rural economic development through the management of local assets and community empowerment. This study aims to examine the role of BUMDes Tawangrejo in improving the local economy through the management of Pasar Tawang in Tawangrejo Village, Kunduran District, Blora Regency. This research applies a descriptive qualitative method using both primary and secondary data sources. Primary data were collected through observations, unstructured interviews, and documentation involving key informants selected through purposive sampling, including BUMDes administrators, market tenants, operational staff, and village government officials. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data collection, data condensation, data display, and conclusion drawing. The results show that BUMDes Tawangrejo contributes to local economic development by optimizing village assets through the provision of affordable rental shops, encouraging community participation, and applying cooperative, transparent, accountable, and sustainable management principles. The existence of Pasar Tawang creates business opportunities, increases economic activities at the village level, and contributes to village original income. However, several challenges remain, such as low community purchasing power and the absence of traditional market-day activities. Therefore, strengthening adaptive management strategies based on local socio-cultural conditions is essential to enhance the sustainability of rural economic development.